Multilateral Disciplines for Investment-Related Policies - Hoekman, Bernard M. 1959- (The World Bank, 1999)
June 1999 - Is there a strong case for developing countries to support the creation of a multilateral agreement on investment? Probably not. Existing agreements offer ample scope for liberalizing foreign direct investment in the area that matters most to developing countries: services. Hoekman and Saggi evaluate the potential benefits of international disciplines on policies toward foreign direct investment for developing countries. They conclude that the case for initiating negotiations on investment policies is weak, at present. Negotiating efforts that center on further liberalizing market access on a nondiscriminatory basis-especially for services-are likely to be more fruitful in terms of economic welfare and growth. Existing multilateral instruments, although imperfect, are far from fully exploited and provide significant opportunities for governments opening further access to markets. Hoekman and Saggi conclude that priority should be given to expanding coverage of the General Agreement on Trade in Services (GATS) before seeking to negotiate general disciplines on investment policies. This paper-a product of Trade, Development Research Group-is part of a larger effort in the group to prepare for the next round of WTO negotiations. The authors may be contacted at bhoekman@worldbank.org or ksaggi @mail.smu.edu